Management of Panfacial Fracture - Ali, Kausar; Lettieri, Salvatore C. (Seminars in Plastic Surgery, 2017)
Traumatic panfacial fracture repair is one of the most complex and challenging reconstructive procedures to perform. Several principles permeate throughout literature regarding the repair of panfacial injuries in a stepwise fashion. The primary goal of management in most of these approaches is to restore the occlusal relationship at the beginning of sequential repair so that other structures can fall into alignment. Through proper positioning of the occlusion and the mandibular-maxillary unit with the skull base, the spatial relationships and stability of midface buttresses and pillars can then be re-established. Here, the authors outline the sequencing of panfacial fracture repair for the restoration of anatomical relationships and the optimization of functional and structural outcomes.
Keywords: panfacial fracture; facial trauma; sequencing repair; occlusion restoration; spatial relationships of midface and mandible